Plant signals differentially affect rhizosphere nematode populations - Mathesius, Ulrike (J Exp Bot, 2021)
This article comments on: Sikder MM, Vestergård M, Kyndt T, Fomsgaard IS, Kudjordjie EN, Nicolaisen M. 2021. Benzoxazinoids selectively affect maize root-associated nematode taxa. Journal of Experimental Botany 72,3835–3845.